Correlation of zinc intake with hair zinc levels and appetite in children aged 2-3 years in Jakarta - Anin Ika Rosa; Diana Sunardi; Novi Silvia Hardiany (Indonesian Nutrition Association, 2022)
Background: Children under five years experience rapid growth and development, so that adequate nutritional intake is very important. Zinc is essential for child development and growth. Childrenâ€™s zinc requirements are fulfilled from daily food intake that might be affected by Covid-19 pandemic. The aim of this study is to determine the correlation between zinc intake with hair zinc level and appetite in children aged 2-3 years in Jakarta. Methods: This cross-sectional study was carried out from September to October 2020 in Kampung Melayu, Jakarta. Seventy children aged 2-3 years were taken using total population sampling method. Interviews were conducted to obtain characteristic data and zinc intake using semi quantitative-food frequency questionnaire (SQ-FFQ). Appetite were assessed using VAS appetite questionnaire. Hair samples were collected to check level of hair zinc. Spearman correlation was performed using SPSS. Results: Median of zinc intake was 6 (1,2-22,5) mg/day, with 20% of the subjects had insufficient zinc intake. The median hair zinc value was 132 (30-451) Âµg/g, with 17,1% subjects zinc insufficient. The median of VAS appetite score was 54,5 mm. There were no significant correlation between zinc intake and hair zinc level (r = -0.077, p = 0.528). A weak positive correlation was found between appetite and hair zinc levels (r = 0,247, p = 0,039). Conclusion: Zinc intake in children aged 2-3 years had no significant correlation with hair zinc level, and appetite had a weak positive correlation with hair zinc level.